Phenomena Occurring in Nanostructured Stainless Steel 316LVM during Annealing under High Hydrostatic Pressure. Issue 1 (24th May 2018) - Krawczynska, Agnieszka T.; Gierlotka, Stanislaw; Suchecki, Przemyslaw; Setman, Daria; Adamczyk‐Cieslak, Boguslawa; Gloc, Michal; Chrominski, Witold; Lewandowska, Malgorzata; Zehetbauer, Michael
Abstract : The aim of the study is to demonstrate the impact of high hydrostatic pressure annealing on the grain boundary character, precipitation rate, and susceptibility to intergranular corrosion of nanostructured austenitic stainless steel 316LVM. To this end, samples of an austenitic stainless steel are deformed by high pressure torsion and subsequently annealed at 900 °C for 10 min under a pressure of 2, 6 GPa and, for comparison, under atmospheric pressure. The resulting microstructures are examined using electron beam scattering diffraction, and transmission and scanning electron microscopy. It is shown that the pressure applied during annealing leads to a higher percentage of high‐angle grain boundaries than does atmospheric pressure. Moreover, it promotes the coexistence of two orientations, <111> and <100>, whereas atmospheric supports mainly <111>. High pressure hinders the growth of carbides, but drastically increases their number compared with atmospheric pressure annealing. As a consequence, the highest number of Cr23 C6 carbides are present in the sample annealed under 6 GPa, making this sample susceptible to intergranular corrosion. Abstract : This study demonstrates the impact of high hydrostatic pressure annealing on the grain boundary character, precipitation rate, and susceptibility to intergranular corrosion of a nanostructured austenitic stainless steel. Results show that annealing under hydrostatic pressure makes it possible to better control the microstructure transformation than conventional annealing while considering low‐angle grain boundary fraction, texture, precipitate size, and chemical composition.